Revision of Capsaloides (Monogenea: Capsalidae) with a redescription of C. magnaspinosus Price, 1939 from the nasal tissue of Tetrapterus audax (Istiophoridae) collected off Nelson Bay, New South Wales, Australia - Chisholm, Leslie A.; Whittington, Ian D. (Zootaxa, 2006)
Capsaloides magnaspinosus (Monogenea: Capsalidae) is redescribed from whole mounts and scanning electron micrographs of material collected from the nasal tissue of the striped marlin, Tetrapterus audax (Philippe, 1887), off Nelson Bay, New South Wales, Australia. This represents a new host and locality record for this capsalid species. Capsaloides is revised based on the examination of type-material and published descriptions. We consider 7 of the 10 previously described species to be valid. Some characters, such as depth of the posterior notch of the body, which were used previously to discriminate between species of Capsaloides, appear to be questionable. Careful examination of type-material has led us to propose that C. istiophori, C. marielenae and C. tetrapteri are synonyms of C. perugiai. The possibility that C. cristatus and C. hoffmannae are synonymous with C. sinuatus is also discussed.